Advancing preconception health in the United States: strategies for change. (1st October 2016) - Verbiest, Sarah; McClain, Erin; Woodward, Suzanne
Abstract: In January 2015, the US Preconception Health and Health Care Initiative (PCHHC) established a new national vision that all women and men of reproductive age will achieve optimal health and wellness, fostering a healthy life course for them and any children they may have. Achieving this vision presents both challenges and opportunities. This manuscript describes the reasons why the US needs to prioritize preconception health as well as its efforts historically to advance change. The authors share lessons from past work and current strategies in the US to reach this ambitious goal.